The Impact of brand experience on brand loyalty: selected Caltex retail site - Padayachee, Priyanka (The IIE, 2016)
The study aimed to explore the impact of brand experience on brand loyalty, focusing specifically on three Caltex retail sites: Clairwood, Hillcrest and Warner Beach. The brand experience created within each site was explored. Consumers’ desires, in terms of brand experience and the effect of brand experience on brand loyalty were also examined. A qualitative approach was employed by this study. The data was collected through self-administered semi-structured interviews, questionnaires and customer journey maps. The semi-structured interview were aimed at Caltex retailers, giving the researcher an internal perspective, followed by consumer questionnaires centered on understanding consumers interpretations and expectations of brand experience. The consumers’ loyalty towards their relevant sites was also reviewed. Customer journey maps for were drawn out, which gave the researcher first hand exposure to each site’s brand experience. The research revealed that varying approaches to brand experience results in varied levels of brand loyalty. In addition to this, there is no consistency between the three Caltex sites, with reference to brand experience.
Theses
Keywords: Brand experience; Brand loyalty; Clairwood Caltex retail; Hillcrest Caltex retail; Warner beach Caltex retail